2012
DOI: 10.1016/j.bcp.2012.06.010
|View full text |Cite
|
Sign up to set email alerts
|

DEC1 binding to the proximal promoter of CYP3A4 ascribes to the downregulation of CYP3A4 expression by IL-6 in primary human hepatocytes

Abstract: In this study, we provided molecular evidences that IL-6 contributed to the decreased capacity of oxidative biotransformation in human liver by suppressing the expression of CYP3A4. After human hepatocytes were treated with IL-6, DEC1 expression rapidly increased, and subsequently, the CYP3A4 expression decreased continuously. Furthermore, the repression of CYP3A4 by IL-6 occurred after the increase of DEC1 in primary human hepatocytes. In HepG2 cells, knockdown of DEC1 increased the CYP3A4 expression and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Moreover, CYP3A4 transcription is affected by cytokines and glucocorticoids; for example, it was recently demonstrated that incubation of human hepatocytes with interleukin 6 (IL‐6) alone 62 or in combination with interleukin‐1β (IL‐1 β) caused a downregulation of CYP3A mRNA expression, 63 and that dexamethasone led to an upregulation 64 . However, to date, there is little or no evidence of an influence of genetic variants in genes encoding cytokines influencing CYP3A activity.…”
Section: Impact Of Genes With Indirect Impact On Cyp3a Activitymentioning
confidence: 99%
“…Moreover, CYP3A4 transcription is affected by cytokines and glucocorticoids; for example, it was recently demonstrated that incubation of human hepatocytes with interleukin 6 (IL‐6) alone 62 or in combination with interleukin‐1β (IL‐1 β) caused a downregulation of CYP3A mRNA expression, 63 and that dexamethasone led to an upregulation 64 . However, to date, there is little or no evidence of an influence of genetic variants in genes encoding cytokines influencing CYP3A activity.…”
Section: Impact Of Genes With Indirect Impact On Cyp3a Activitymentioning
confidence: 99%
“…HepG2 cells were transfected with vector or PXR shRNA constructs for 12 h, and total RNA and cell lysate were prepared to analyze the expression of CYP3A4, PXR and GAPDH by qRT-PCR and Western blotting, respectively. 64 We previously demonstrated that DEC1 transcriptionally downregulates the CYP3A4 expression in response to IL-6, 33 indicating for the first time that DEC1 is involved in metabolizing xenobiotics, including the vast majority of clinically used drugs, environmental pro-carcinogens and toxins. Vector or human PXR was transfected into HepG2 cells for 48 h, and the cells were treated with GA (1 μM) for an additional 24 h. Total RNA and lysates were prepared to analyze the expression levels of CYP3A4, PXR and GAPDH by qRT-PCR and Western blotting, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, it translocates from the cytosol to the nucleus, where it forms a heterodimer with RXR (retinoid X receptor) and binds to the promoter regions of its target genes. 33 Gambogic acid (GA) is a small molecule that is present in the traditional Chinese medicine gamboges, and it has been used for hundreds of years in China. 19 The transcriptional activity of activated PXR also requires interaction with different co-activators, including HNF4α, 20 peroxisome proliferator-activated receptor-γ co-activator (PGC-1) and steroid receptor co-activator-1 (SRC-1).…”
Section: Introductionmentioning
confidence: 99%
“…pregnane X receptor (PXR; -362/+53) (33), constitutive androstane receptor (CAR) (34), nuclear factor I (-243/-220) (29), differentially expressed in chondrocyte 1 (35) and hepatocyte nuclear factor 4a (HNF4a) (36) have been reported to account for a component of CYP3A4 inter-individual variability.…”
Section: A B a Bmentioning
confidence: 99%